Bioequivalence of fixed‐dose combinations of dapagliflozin and metformin with single‐component tablets in healthy subjects and the effect of food on bioavailability. Issue 2 (20th October 2015) - de Bruin, Tjerk W.A.; Reele, Stots; Hamer‐Maansson, Jennifer E.; Parikh, Shamik; Tang, Weifeng
Abstract: The pharmacokinetics (PK) of dapagliflozin and metformin administered as fixed‐dose combination (FDC) tablets (2.5 mg dapagliflozin/850 mg metformin or 5 mg dapagliflozin/1000 mg metformin) or as separate tablets in healthy subjects were evaluated in 2 separate studies. Study 1 evaluated PK by measuring mean ratios of area under the plasma concentration–time curve (time zero to infinity [AUCinf ]), AUC from zero to time of last measurable concentration (AUC0–t ), and maximum observed plasma concentration (Cmax ) for single‐component or FDC tablets following a non‐high‐fat meal. Mean ratios of AUCinf, AUC0–t, and Cmax for FDC or single‐component dapagliflozin and metformin tablets were close to unity. In study 2, AUCinf, AUC0–t, and Cmax for the FDC tablet were obtained fasting and after a high‐fat meal. Dapagliflozin 5 mg and metformin 1000 mg geometric mean Cmax was increased in the fasted versus fed state (61.9 vs 43.9 and 1600 vs 1330 ng/mL, respectively), but AUC0–t was similar (267 and 265 and 11 000 and 10 600 ng · h/mL, respectively). In summary, FDC tablets were bioequivalent to single‐component tablets, and total absorption (AUC) was similar for non‐high‐fat and high‐fat meals.